Thymic Squamous Cell Carcinoma: A Population-Based Surveillance, Epidemiology, and End Result Analysis - Yang, Xudong; Zhao, Kejia; Li, Chuan; Yang, Yanbo; Guo, Chenglin; Pu, Yi; Liu, Lunxu (Frontiers in Oncology, 2020)
Objectives Thymic squamous cell carcinoma (TSCC) is a rare neoplasm that has been sparsely cited in the literature. The aim of this study was to determine disease characteristics and prognostic factors of patients in a Surveillance, Epidemiology, and End Results (SEER) analysis. Methods Cases from 1990–2016 were retrieved from the SEER database and demographics, treatments, and survival outcomes were analyzed. Results The TSCC accounted for 72.4% of the thymic carcinomas and 7.2% of thymic tumors. The 276 patients (165 men) selected for analysis had a median age of 65 (24–85) years, and 201 patients were diagnosed with Masaoka-Koga stage III/IV. The median survival of TSCC was 59 months with a 49.0% 5-year OS rate, a better prognosis than lymphoepithelioma-like carcinoma (32.1%) and undifferentiated carcinoma (33.3%). Multivariate analysis revealed the Masaoka-Koga stage (p = 0.003) and surgical types (complete resection, incomplete resection, and none; p < 0.001) were determinants of survival. Complete resection had the best prognosis with a 72.7% 5-year OS rate. Chemotherapy was an independent protective factor (HR = 0.555, 95% CI 0.347–0.886; p = 0.014) though poor survival was showed in univariate analysis. And the survival benefit of chemotherapy was validated in PSM analysis (3-year OS rate was 77.7% with chemotherapy vs. 52.8% without chemotherapy; p = 0.014). Conclusions TSCC was frequently diagnosed in older patients with advanced Masaoka-Koga stage and had more favorable survival than other subtypes of thymic carcinomas. Complete resection is the preferred treatment. Masaoka-Koga stage and chemotherapy had a strong association with prognosis.